Penerapan Metode Multisensori pada Siswa Disleksia SDN Bantar Jati 9 Kota Bogor - Nur Assyah; Yuli Mulyawati; Rukmini Handayani (STKIP Andi Matappa Pangkep, 2022)
Reading is the foundation of learning. Referring to the results of initial observations with class teachers in one of the elementary schools, it turns out that there are still grade 3 students who cannot read, and do not even recognize letters at all. The method used for dyslexic students is the multisensory method. This research was conducted using a Case Study Qualitative Research Approach. The purpose of this study was to analyze the application of the multisensory method to dyslexic students. The subject in this study was one of the third grade students of SDN Bantar Jati 9, Bogor City. Data collection in this study was carried out by conducting observations, interviews, and documentation. Data analysis techniques with data reduction, data presentation and verification. The results showed that dyslexic students had difficulty recognizing letters. Multisensory can help dyslexic students in learning to read. The modalities in the multisensory method are based on the VAKT. Visual aspects are seen when students are asked to look at letter cards, auditory is when the teacher mentions the sound of the letters and is repeated by students, kinesthetic & tactile is when students feel the letter cards and sort letters into a word.